Design and Development of a 2 × 2 Array Piezoelectric–Electromagnetic Hybrid Energy Harvester - Bing Han; Shubin Zhang; Jianbin Liu; Yanfeng Jiang (Micromachines, 2022)
Energy harvesting technology is regarded as a feasible solution for the continuous power supply of microelectronic devices. Efforts have been made to improve the output power of all kinds of energy harvesting devices. This paper reports a 2 × 2 array piezoelectric–electromagnetic hybrid energy harvester that achieves high power output through the combination of piezoelectric and electromagnetic conversion. The harvester included four piezoelectric–electromagnetic hybrid modules, each of which consisted of a piezoelectric sheet, a permanent magnet and a wound coil. The permanent magnet, also serving as the mass block of the cantilever beam when subjected to external stimulus, contributed to a large displacement of the vibration and generated high output power. At an acceleration of 1 g and a resonance frequency of 70.4 Hz, the measured maximum output power of the hybrid energy harvester was 66.08 mW, of which the piezoelectric and electromagnetic portions were 56.96 and 9.12 mW, respectively. Furthermore, in a charging experiment, a capacitor of 23.5 mF was charged to 11.5 V within 20 s, which demonstrates a practical application of the hybrid energy harvester for microelectronic devices.